Antibiotic knowledge, attitudes and practices: new insights from cross-sectional rural health behaviour surveys in low-income and middle-income South-East Asia. Issue 8 (20th August 2019) - Haenssgen, Marco J; Charoenboon, Nutcha; Zanello, Giacomo; Mayxay, Mayfong; Reed-Tsochas, Felix; Lubell, Yoel; Wertheim, Heiman; Lienert, Jeffrey; Xayavong, Thipphaphone; Khine Zaw, Yuzana; Thepkhamkong, Amphayvone; Sithongdeng, Nicksan; et al.
Abstract : Introduction: Low-income and middle-income countries (LMICs) are crucial in the global response to antimicrobial resistance (AMR), but diverse health systems, healthcare practices and cultural conceptions of medicine can complicate global education and awareness-raising campaigns. Social research can help understand LMIC contexts but remains under-represented in AMR research. Objective: To (1) Describe antibiotic-related knowledge, attitudes and practices of the general population in two LMICs. (2) Assess the role of antibiotic-related knowledge and attitudes on antibiotic access from different types of healthcare providers. Design: Observational study: cross-sectional rural health behaviour survey, representative of the population level. Setting: General rural population in Chiang Rai (Thailand) and Salavan (Lao PDR), surveyed between November 2017 and May 2018. Participants: 2141 adult members (≥18 years) of the general rural population, representing 712 000 villagers. Outcome measures: Antibiotic-related knowledge, attitudes and practices across sites and healthcare access channels. Findings: Villagers were aware of antibiotics (Chiang Rai: 95.7%; Salavan: 86.4%; p<0.001) and drug resistance (Chiang Rai: 74.8%; Salavan: 62.5%; p<0.001), but the usage of technical concepts for antibiotics was dwarfed by local expressions like 'anti-inflammatory medicine' in Chiang Rai (87.6%; 95% CI 84.9% to 90.0%) and 'ampi' in Salavan (75.6%; 95% CI 71.4% to 79.4%). Multivariate linear regression suggested that attitudes against over-the-counter antibiotics were linked to 0.12 additional antibiotic use episodes from public healthcare providers in Chiang Rai (95% CI 0.01 to 0.23) and 0.53 in Salavan (95% CI 0.16 to 0.90). Conclusions: Locally specific conceptions and counterintuitive practices around antimicrobials can complicate AMR communication efforts and entail unforeseen consequences. Overcoming 'knowledge deficits' alone will therefore be insufficient for global AMR behaviour change. We call for an expansion of behavioural AMR strategies towards 'AMR-sensitive interventions' that address context-specific upstream drivers of antimicrobial use (eg, unemployment insurance) and complement education and awareness campaigns. Trial registration number: Clinicaltrials.gov identifier NCT03241316 .